IMPLEMENTATION OF SOCIAL JUSTICE PRINCIPLES IN ECONOMIC LAW FOR THE PROTECTION OF THE POOR, NEGLECTED CHILDREN, AND VULNERABLE GROUPS: A LITERATURE REVIEW OF POLICIES AND PRACTICES IN INDONESIA - Gunawan Widjaja; Songga Aurora Abadi; Brian Matthew (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyse the implementation of the principle of social justice in economic law as an effort to protect the poor, abandoned children, and vulnerable groups in Indonesia. This study uses a desk research method with a qualitative and normative approach, examining various laws and regulations, government policies, and relevant scientific literature. The results show that the state has developed a number of legal instruments and social protection programmes, such as the Family Hope Programme (PKH), Non-Cash Food Assistance (BPNT), and National Health Insurance (JKN), which are based on the constitutional mandate, particularly Article 34 of the 1945 Constitution. However, the effective implementation of these policies still faces challenges such as weak law enforcement, complicated bureaucracy, budget constraints, and lack of coordination between institutions. Therefore, there is a need to strengthen the synergy between the government, private sector, NGOs and civil society, as well as bureaucratic reform and stricter supervision to ensure the protection of vulnerable groups is optimal. This research is expected to contribute to the development of a more inclusive and socially just economic legal policy in Indonesia.